Pseudodynamic tests on a full-scale 3-storey precast concrete building: behavior of the mechanical connections and floor diaphragms - Bournas, Dionysios A.; Negro, Paolo; Molina, Francisco J. (Elsevier, 2013)
A full-scale three-storey precast building was tested under seismic conditions at the European Laboratory for Structural Assessment in the framework of the SAFECAST project. The unique research opportunity of testing a complete structural system was exploited to the maximum extent by subjecting the structure to a series of pseudodynamic (PsD) tests and by using four different structural layouts of the same mock-up, while 160 sensors were used to monitor the global and local response of each layout. Dry mechanical connections were adopted to realize the joints between: floor-to-floor, floor-to-beam, wall-to-structure; column (and wall)-to-foundation and beam-to-column. Particular emphasis was given to the seismic behavior of mechanical beam–column connections, as well as to the response of floor diaphragms. Thus, the in-plane rigidity of three pretopped diaphragms with or without openings was assessed. In addition, two types of beam-to-column connections were investigated experimentally, namely hinged beam–column connections by means of dowel bar and emulative beam–column joints by means of dry innovative mechanical connections. Therefore, the seismic behavior of floor diaphragms and pinned beam–column connections in a multi-storey precast building was addressed experimentally. The results demonstrated that the proposed new beam-to-column connection system is a viable solution toward enhancing the response of precast RC frames subjected to seismic loads, in particular when the system is applied to all joints and quality measures are enforced in the execution of the joints.